Community Development Quotas and Support of Small-Scale Fisheries as Two Key Concepts for Blue Growth in Fisheries - Sulanke, Erik; Rybicki, Sandra (Frontiers in Marine Science, 2021)
Blue Growth has become one of the key topics of ocean management. It is defined as a holistic framework for an environmentally friendly and socio-economically sustainable development of ocean-related activities with a special emphasis on technological innovation. Capture fisheries are widely considered to have no substantial growth potential and consequently are not subject to the European Union’s Blue Growth strategy. In our review, we, however, argue that capture fisheries should play an essential role in national Blue Growth strategies. We identified two interconnected management strategies to foster Blue Growth in fisheries, a) the implementation of Community Development Quota (CDQ) systems and b) the support of small-scale fisheries (SSF). They hold the potential to benefit fishery-dependent coastal communities and therefore counteract consolidations in the fishing sector. Additionally, they provide the possibility to improve quota access for small-scale fishermen. Besides having better access to quota, the future of SSF depends on sources of public funding for technical improvement and innovation as well as increased representation in the management. In this perspective, we present different cases that successfully implemented CDQs (the Alaska pollock fishery) or have considerable potential to implement CDQ programs or improve their current approaches (United Kingdom, Ireland, and Iceland). We further discuss examples for successful management strategies to support SSF directly. If these aspects are considered in a Blue Growth strategy, the survival of fishery-dependent communities could be assured, and SSF could develop from predominantly part-time or subsistence fisheries to a full-time occupation. By those means, they would be part of a fostering Blue Economy and strengthen environmentally friendly and socio-economically sustainable fishing practices in Europe.